Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1080/09658416.2021.1969404
|View full text |Cite
|
Sign up to set email alerts
|

Are individual differences in cognitive abilities and stylistic preferences related to multilingual adults’ performance in explicit learning conditions?

Abstract: Are individual differences in cognitive abilities and stylistic preferences related to multilingual adults' performance in explicit learning conditions?, Language Awareness,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 50 publications
(73 reference statements)
0
4
0
Order By: Relevance
“…Specifically, PWM appears to be an important predictor of vocabulary, grammar and reading at lower levels of proficiency and/or in novice learners (Hummel, 2009;Serafini & Sanz, 2016), whereas the role of WM at higher levels is less clear. Linck et al (2013) reported a positive influence of PWM on long-term listening and reading attainment in a group of advanced learners, whereas other studies with experienced learners at advanced levels found no effect of PWM on vocabulary and grammar knowledge (Linck & Weiss, 2011) and no association between EWM and knowledge of a grammatical structure of high learning difficulty (Roehr-Brackin et al, 2021).…”
Section: Language Learning Aptitude and Wm As Predictors Of L2 Attain...mentioning
confidence: 89%
See 1 more Smart Citation
“…Specifically, PWM appears to be an important predictor of vocabulary, grammar and reading at lower levels of proficiency and/or in novice learners (Hummel, 2009;Serafini & Sanz, 2016), whereas the role of WM at higher levels is less clear. Linck et al (2013) reported a positive influence of PWM on long-term listening and reading attainment in a group of advanced learners, whereas other studies with experienced learners at advanced levels found no effect of PWM on vocabulary and grammar knowledge (Linck & Weiss, 2011) and no association between EWM and knowledge of a grammatical structure of high learning difficulty (Roehr-Brackin et al, 2021).…”
Section: Language Learning Aptitude and Wm As Predictors Of L2 Attain...mentioning
confidence: 89%
“…Second, including measures of both PWM and EWM seems advisable, given that the two components have been shown to contribute differently to L2 proficiency (Linck et al, 2014). Third, taking into account learners' L2 proficiency level appears to be of critical importance (e.g., Hummel, 2009;Linck et al, 2013;Roehr-Brackin et al, 2021;Serafini & Sanz, 2016).…”
Section: Language Learning Aptitude and Wm As Predictors Of L2 Attain...mentioning
confidence: 99%
“…Compared with the average response time in Cognitive Style Analysis, the median value could minimise the effect from outliers [82]. The VICS test has been successfully applied by numerous studies in VI cognitive style dimension classification [8,44,58,98,103,106]. Considering that the VICS test makes up for some of the defects of the previous measures, we chose it as the cognitive assessment tool for our research.…”
Section: Cognitive Style Measurementsmentioning
confidence: 99%
“…Group averages cannot tell us, for instance, if explicit knowledge, learning and teaching work equally well for all learners at all times, regardless of their cognitive abilities, attitudes or personality traits. There is evidence suggesting that individuals may well differ as to the extent to which they can and will successfully construct explicit knowledge and draw on explicit learning, depending on their prior language learning experience (Roehr & Gánem-Gutiérrez, 2009; Roehr-Brackin et al, 2021), their level of proficiency in the language under study (Butler, 2002; Elder et al, 1999), the typological distance between the first language (L1) and L2 under study (Elder & Manwaring, 2004), their language learning aptitude (Alderson et al, 1997; Elder et al, 1999; Roehr & Gánem-Gutiérrez, 2009) 2 , working memory capacity (Linck & Weiss, 2011; Roehr & Gánem-Gutiérrez, 2009; Serafini, 2017; Serafini & Sanz, 2016), or cognitive style (Ziętek & Roehr, 2011). What we do not have are studies that bring together all of these variables in a single research design and include measures of explicit and/or implicit knowledge and learning as well.…”
Section: Introductionmentioning
confidence: 99%